Synthesis, Characterization, and In Vitro Drug Delivery of Chitosan-Silica Hybrid Microspheres for Bone Tissue Engineering. (14th August 2019) - Niu, Niu; Teng, Shu-Hua; Zhou, Hua-Jian; Qian, Hai-Sheng
Abstract : Chitosan-silica (CS-SiO2 ) hybrid microspheres were prepared through the combined process of sol-gel and emulsification-crosslinking. Their composition, morphology, in vitro bioactivity, and drug release behavior were investigated. The results showed that, when 20 wt% SiO2 was incorporated, the as-prepared CS-SiO2 hybrid microspheres exhibited a regular spherical shape, a high dispersity, and a uniform microstructure. Their average particle diameter was determined to be about 24.0 μ m. The in situ deposited inorganic phase of the hybrid microspheres was identified as amorphous SiO2, and its actual content was determined by the TG analysis. As compared with the pure chitosan microspheres, the CS-SiO2 hybrid microspheres displayed a greatly improved in vitro bioactivity. Vancomycin hydrochloride (VH) was selected as a model drug. It was demonstrated that the CS-SiO2 hybrid microspheres presented a good capacity for both loading and sustained release of VH. Moreover, the increase of the SiO2 content efficiently slowed down the drug release rate of the CS-SiO2 hybrid microspheres.